2015
DOI: 10.1155/2015/123682
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Malaria Occurrence in Wolaita Zone, Southern Ethiopia: Retrospective Cross-Sectional Study

Abstract: Background. Malaria is a major public health problem in Ethiopia. The trend of malaria occurrence remains unknown in the study area. This study is aimed at determining the last five years' trend of malaria occurrence from 2008/09 to 2012/13 in Wolaita Zone, Southern Ethiopia. Methods. A health facility-based retrospective study was conducted in Wolaita Zone from March to August, 2014. Five years' laboratory confirmed malaria record review was made from six health centers. Result. A total of 105,755 laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
14
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 9 publications
16
14
9
Order By: Relevance
“…However, these ndings are less than similar reports from 10 years data documented in Metema Hospital, northwest Ethiopia (91%) [24], and sub-Saharan African countries, where 99.7% of estimated malaria cases were due to P. falciparum [25], which could be related The study also revealed higher positivity rate of malaria among males (58.1%) than females (41.9%). This nding is in agreement with other studies conducted in various areas of Ethiopia, which reported higher malaria prevalence in males than females [15,18,22,27]. Such higher malaria prevalence in males is conceived to be attributed to the fact that males are usually engaged in outdoor activities that put them at greater risk of contracting the disease [22,28].…”
Section: Discussionsupporting
confidence: 92%
“…However, these ndings are less than similar reports from 10 years data documented in Metema Hospital, northwest Ethiopia (91%) [24], and sub-Saharan African countries, where 99.7% of estimated malaria cases were due to P. falciparum [25], which could be related The study also revealed higher positivity rate of malaria among males (58.1%) than females (41.9%). This nding is in agreement with other studies conducted in various areas of Ethiopia, which reported higher malaria prevalence in males than females [15,18,22,27]. Such higher malaria prevalence in males is conceived to be attributed to the fact that males are usually engaged in outdoor activities that put them at greater risk of contracting the disease [22,28].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding age, the highest affected age group was > 15 years accounted for 54% followed by 5-14 age group 23.5% while the least affected age group was < 1 year in both sexes and the most frequently reported species in all age groups were P. vivax. The highest malaria prevalence in the adult age group obtained was in agreement with other findings reported across Ethiopia [19,22,27,28]. Whereas a finding from Arsi Negelle [29] showed that highly affected age group was 0-5 years followed by 16-20 years old.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, Plasmodium infection was nearly equal with only slight variation among males and females which was comparable with a study conducted in Wolaita zone [19]. This finding was in contrast with the majority of the study done in Ethiopia [25,26] where males were highly affected by malaria than females.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This was in agreement with a study conducted in Kola Diba Health Centre [4]. However, in contrast to this finding, the study conducted in Wolita showed high malaria positivity in 5–14 year olds [17]. The reason why malaria affects the 15–45 age group in Kombolcha might be because these age groups are productive and as a result they are actively involved in industrial and agricultural activities.…”
Section: Discussionsupporting
confidence: 90%